Going nuclear? Think again - Abd Razak, Dzulkifli (2006)
TWO decades ago last week, the world witnessed its worst nuclear disaster at the Ukraine nuclear reactor site, Chernobyl, then part of the Soviet Union. Twenty years on, the environment is still contaminated, especially in the socalled "exclusion zone", 30km around the plant. This includes plants, animals, trees, groundwater sources and also hundreds of abandoned vehicles, ranging from Sovietmade Lada cars to helicopters that were used to fight the blazing reactors.